Determining the Impacts of Stone Quarrying on Riparian Vegetation of River Molo in Rongai Sub-County, Nakuru County, Kenya - Kipyator Dennis (Kabarak University, 2025)
Abstract The contribution made by stone quarrying to the Gross Domestic Product (GDP) in many countries globally is enormous. Whether small or large-scale, stone quarrying is inherently disruptive and can cause detrimental effects on riparian vegetation which is considered the most vulnerable and fragile ecosystem. This study sought to determine the status of riparian vegetation between 2000- 2023 along river Molo, assess the level of awareness on the impacts of stone quarrying on riparian vegetation, determine the perceived effects of stone quarry works on riparian vegetation of R. Molo and recommend effective measures to curb the negative impacts of stone quarrying activities. A descriptive survey design was adopted where stratified sampling was used to select 404 Visoi, Soin and Mosop wards were 404 head of households were randomly chosen. Fifteen key informants and five quarry sites were purposively sampled for interviews and field visit respectively. Questionnaires, interview schedules and Geographical Information System and Remote Sensing were the main instruments where spatial data obtained were analyzed using ArcMap GIS by employing Normalized Difference Vegetation Index (NDVI) and time series analysis. The data from questionnaires and interviews schedules were analyzed using Ms. Excel and Statistical Package for the Social Sciences (SPSS version 27) employing descriptive statistics and correlation. The findings revealed a significant decline in riparian vegetation attributed to land use changes linked with quarrying activities. The land use analysis showed barren lands along the riparian areas indicating the ongoing quarrying activities, with grasslands and shrub lands dominating the landscape. Notably, (90%) of respondents were unaware of the impacts of stone quarrying on the riparian vegetation implying the need for more public participation. There was a significant negative correlation between public participation and stone quarrying impacts at p= -0.412 implying that low level of public participation on stone quarrying led to increased destruction of riparian vegetation. The study found a strong perception among respondents that quarrying led to changes in riparian vegetation cover, felling of trees and grasses, reduced natural regeneration and increased soil erosion. The likert type scale demonstrated a higher mean score for rehabilitation and reclamation of quarry sites, planting of trees and grass, promotion of public participation, proper disposal of quarry overburden and enactment of laws to govern quarrying in Nakuru County. According to the study these approaches can be regarded as best practices for mitigating the negative impacts of stone quarrying on riparian vegetation.
Full text
Keywords: Geographical Information System; Normalized Difference Vegetation Index; Riparian vegetation; Quarrying